48 Detection and Management of Atrial Fibrillation in the Pacing Clinic. (3rd June 2016) - Gilmore, Mark; Barry, James; Rees, Paul; Churchouse, Wendy
Abstract : Purpose: Atrial fibrillation (AF) is a common arrhythmia and is a significant risk factor for stroke. Oral anticoagulants are effective treatments which substantially lower the risk of stroke in patients with AF. Sadly many patients are not prescribed anticoagulants. Modern pacemakers are capable of acting as cardiac monitors and store episodes of AF or mode switch events (MS) which may indicate the presence of AF. Utilisation of this pacemaker technology by cardiac physiologists could improve early detection and treatment of AF improving patient outcomes and reduce stroke risk. The audit aimed to investigate the frequency of AF in our pacemaker population and determine whether appropriate action had been taken to identify the episodes and notify the general practitioner (GP). Method: A retrospective analysis of pacing clinic notes was made for 100 consecutive patients attending pacemaker interrogation. 12 NEW cases of AF were diagnosed from the utilisation of pacemaker technology. 1 (8%) of the 12 was already anticoagulated and documented. 2 (17%) patients - no clear documentation of action taken e.g. GP informed. 9 (75%) patients - clear documentation that GP had been informed and action had been taken. 17 patients had episodes of MS greater than 30 s. 10 (59%) had intracardiac electrogram monitoring (EGM) activated and returned to clinic in two months time. 1 (6%) patient had an older device with no EGM monitoring available and was fitted with a holter monitor. 6 (35%) patients had no clear plan documented. A repeat retrospective analysis of 100 patients was made 6 months later and the results showed: 19 NEW cases of AF were diagnosed. 3 (16%) of the 19 was already anticoagulated and documented. 16 (84%) patients - clear documentation that GP had been informed and action had been taken. All patients were appropriately managed. 16 patients had episodes of MS greater than 30 s. 13 (81%) had EGM activated and returned to clinic in two months time. 1 (6%) patient had an older device with no EGM monitoring available and was already anticoagulated. 2 (13%) patients were nearing battery replacement and EGM storage was not activated to conserve battery life. Conclusion: AF is highly prevalent in our pacemaker population. Utility of pacemaker technology by cardiac physiologists improved early detection and treatment of AF in 83% patients. This improved patient outcomes and reduced stroke risk significantly. Future improvements included a clear, auditable pathway for physiologists when AF is suspected/identified to ensure this is consistently communicated to patients and their doctors. This is reflected from the repeat retrospective study which has shown raising awareness can have an impact.